Penerapan Model Pembelajaran Inquiry Based Learning pada Mata Pelajaran Al-Islam Untuk Meningkatkan Keterampilan Kognitif Siswa Kelas XII SMA Muhammadiyah 1 Bandar Lampung - Salman Lintang Firdaus; Khoironi; Mashdaria Huwaina (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2025)
The field of Islamic Studies can be said to be one of the compulsory fields of study in the Islamic, Muhammadiyah, and Arabic learning program, designed by the MPDM PNF or the Muhammadiyah Elementary and Secondary Education & Non-Formal Education Council, also known as ISMUBA. Islamic studies, similar to Islamic Religious Education, include the Qur'an and Hadith, Fiqh, Aqidah, Morals, and Islamic history. Islamic studies are taught to students with the aim of making them become individuals who are faithful, pious, and have good morals. Meanwhile, cognitive skills are a student's ability to think more deeply, conduct analysis, and solve problems logically. Meanwhile, the Inquiry Learning Model is a learning model that emphasizes students to find out and build their own knowledge. The method used in this study is a qualitative approach method in which data collection uses observation, interviews, and documentation. This study makes Islamic subject teachers and also grade XII students of SMA Muhammadiyah 1 Bandar Lampung as objects and data sources. There are steps in using the Inquiry-Based Learning model, namely: Orientation, formulating problems, formulating hypotheses, collecting data, testing hypotheses, and drawing conclusions. Students' cognitive skills include their abilities in knowledge, understanding, application, analysis, combining, and evaluating a problem or material being presented. The application of the Inquiry-Based Learning model during Al-Islam learning has significantly improved students' cognitive skills. Many students who previously only understood can now analyze and express their opinions.